Mechanisms Decreasing In Vitro Susceptibility to the LpxC Inhibitor CHIR-090 in the Gram-Negative Pathogen Pseudomonas aeruginosa - Caughlan, Ruth E. (American Society for Microbiology, 2012)
Testing P. aeruginosa efflux pump mutants showed that the LpxC inhibitor CHIR-090 is a substrate for MexAB-OprM, MexCD-OprJ, and MexEF-OprN. Utilizing P. aeruginosa PAO1 with a chromosomal mexC::luxCDABE fusion, luminescent mutants arose on medium containing 4 μg/ml CHIR-090, indicating upregulation of MexCD-OprJ. These mutants were less susceptible to CHIR-090 (MIC, 4 μg/ml) and had mutations in the mexCD-oprJ repressor gene nfxB. Nonluminescent mutants (MIC, 4 μg/ml) that had mutations in the mexAB-oprM regulator gene mexR were also observed. Plating the clinical isolate K2153 on 4 μg/ml CHIR-090 selected mutants with alterations in mexS (immediately upstream of mexT), which upregulates MexEF-OprN. A mutant altered in the putative1ribosomal binding site (RBS) upstream of lpxC and overexpressing LpxC was selected on a related LpxC inhibitor and exhibited reduced susceptibility to CHIR-090. Overexpression of LpxC from a plasmid reduced susceptibility to CHIR-090, and introduction of the altered RBS in this construct further increased expression of LpxC and decreased susceptibility to CHIR-090. Using a mutS (hypermutator) strain, a mutant with an altered lpxC target gene (LpxC L18V) was also selected. Purified LpxC L18V had activity similar to that of wild-type LpxC in an in vitro assay but had reduced inhibition by CHIR-090. Finally, an additional class of mutant, typified by an extreme growth defect, was identified. These mutants had mutations in fabG, indicating that alteration in fatty acid synthesis conferred resistance to LpxC inhibitors. Passaging experiments showed progressive decreases in susceptibility to CHIR-090. Therefore, P. aeruginosa can employ several strategies to reduce susceptibility to CHIR-090 in vitro.